Selection and Biosensor Application of Aptamers for Small Molecules - Pfeiffer, Franziska; Mayer, Günter (Frontiers in Chemistry, 2016)
Small molecules play a major role in the human body and as drugs, toxins and chemicals. Tools to detect and quantify them are therefore in high demand. This review will give an overview about aptamers interacting with small molecules and their selection. We discuss the current state of the field, including advantages as well as problems associated with their use and possible solutions to tackle these. We then discuss different kinds of small molecule aptamer-based sensors described in literature and their applications, ranging from detecting drinking water contaminations to RNA imaging.